Owners’ perceptions of dog treat management in Western Romania - Daina, Sorana; Blaga-Petrean, Anamaria; Popescu, Silvana; Pop, Ioana Delia; Mierlita, Daniel; Macri, Adrian (Frontiers in Animal Science, 2025)
IntroductionWithin the broader-than-ever palette of pet foods, dog treats are an assortment sustained by powerful marketing tools and compelling advertising. The wide range and availability of these products often pair with the fondness of owners for their companions, leading to overfeeding them with rewards.MethodsThis study explored owner treat provision behaviors among 890 voluntarily participating dog owners in Western Romania through an online survey conducted between June and November 2023.ResultsThe majority of respondents were women (72%) and younger adults aged 18–24 (39%). Emotional attachment was the primary motivation for providing treats (52%), followed by perceived health benefits (35%) and training purposes (25%). However, 84% of respondents did not account for the caloric value of treats in their dogs' daily diet, and only 16% adjusted their dogs' main meals to compensate for treat provision. Preferences leaned toward treats with dental benefits (58%) and biscuits (52%). Many owners reported offering treats multiple times daily, highlighting the role of treats in owner-dog bonding. Chi-square tests of independence, with Bonferroni-adjusted post-hoc pairwise comparisons, revealed significant associations between treat provision frequency, owner demographics, and dog characteristics. Younger owners (18–24 years) were significantly more likely to provide treats at higher frequencies, with 31.8% giving treats 'multiple times daily' compared to 7.1% of older owners (>55 years) (p<0.002). Similarly, single owners provided treats more frequently, with 31.9% giving treats 'once daily' and 42.1% 'multiple times daily', compared to 7.1% and 22.4%, respectively, among owners in committed relationships (p<0.005). Owners who provided treats less frequently, 'seldom' (80.7%) or 'a few times a week' (87.8%), were more likely to have dogs with an ideal weight, while higher treat frequencies – 'once daily' (40.0%) or 'multiple times daily' (52.7%), were significantly associated with overweight or obese dogs (p<0.003).DiscussionThese findings underscore the importance of educating dog owners on aligning treat provision with caloric requirements and promoting responsible feeding practices. Veterinarians play a critical role in guiding owners toward balanced feeding strategies that incorporate treats into comprehensive dietary plans. Addressing treat provision behaviors is essential to mitigating health risks, improving canine nutrition, and promoting overall well-being.